Analisis Faktor-Faktor Yang Mempengaruhi Audit Delay(Studi Empiris Pada Perusahaan Aneka Industri dan Keuangan di BEI Tahun 2012-2014) - Setyawan, Angga; , Drs. Wahyono, M.A.,Akt (2016)
The purpose of this research is to find out whether the size of the company, auditor reputation, industry classification, firm age, profit and loss are the factors that affect audit delay to various industries and finance in BEI years 2012-2014. Technique of taking sample used is purposive sampling with the number of samples 159 company of various industry and financial listed at BEI period 2012-2014. Analysis of data using multiple linear regression analysis. The result of the research show that the size of the company, auditor reputation and the profit loss company effect on audit delay, while the industry classification and firm age does not effect on audit delay. Keywords: size of the company, auditor reputation, industry classification, firm age, profit and loss company, and audit delay